Pendampingan UMKM Dalam Pembuatan NIB Melalui Sistem Online Single Submission di Kelurahan Karangsari Kota Blitar - Shofiyah Salsabila; Dhiah Permatasari; M. Fikri Abdurrohman; Mentari Clara Dewanti; Siti Aminah (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
Currently, the central government and local governments offer a lot of assistance, in the form of reduced costs in business assistance and training for business behavior, thus requiring business owners to have a Business Identification Number. Business Identification Number or NIB is the identity of business actors issued by the government through the OSS institution after the entrepreneur registers. This identity replaces several previous permits and is one of the prerequisites for obtaining a SIUP (Trade Business License). The NIB consists of a thirteen-digit number in which there is a security and an electronic signature. This NIB is valid as a business identity used by Business Actors to obtain Business Permits and Commercial or Operational Permits including to fulfill the requirements for Business Permits and Commercial or Operational Permits. The mentoring method implemented by the researcher was (1) Survey, (2) Interview, and (3) Focused Discussion. Assistance in making NIB in Karangsari Village will be carried out on April 6, 2022 to April 14, 2022. It is hoped that this NIB assistance can help MSMEs in Karangsari Urban Village to obtain business legality in order to facilitate the processing of other business letters, and show that the business does exist, operates. and worth standing up. The target in this research is about 10 UMKM in Karangsari Urban Village.